The metamorphosis of Mincode constructing a visual identity system for a coalition - Danlay, Marlon John V.
In the 21st century, branding has become increasingly important for any organization. We are living in a time wherein there is a rapid increase in competition and the key to survival is differentiation. Products and services are becoming indistinguishable and competition creates infinite choices. Any organization that wishes to stay in the marketplace is a challenged to become walking brands. Now, companies are faced with the fact that being remembered is harder as each day passes. They must create strong brands for themselves and their products to stand out in the densely crowded marketplace. To be able to this, a company or a coalition needs effective needs an effective visual identity system that communicates well the corporate image and the quality of the products and services being offered. Gaining an interest in logos as I observe them everyday, my production research focused on constructing an appropriate visual identity system for Mindanao Coalition of Development NGO networks ? MINCODE, a coalition of twelve Mindanao NGO networks, for its branding program. My study is suggesting that the coalition's nature, its people, and the problem that I have seen with its current logo are major influences in the design of its visual identity system, made up of a new logo and a visual system that will eventually lead to the creation of a strong MINCODE brand identity. For MINCODE's new logo, I used the design principles simplicity, clarity, and flexibility, ideas which are still alien here in Mindanao and for its visual system, I designed it to be consistent and supportive with the logo
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media arts